IPTEK BAGI MASYARAKAT KELOMPOK PANDE BESI TARIK SIDOARJO - Budijanto Budijanto; Adi Sucipto; Nur Iffah (JPM PAMBUDI, 2017)
Tarik Krian Sidoarjo is one of the areas of agricultural technology and the result pemroduk carpentry most reliable and most turnover compared with other regions. Products produced are tools such as the hoe, trowel, sickles, shovels, machetes, bendo and others. However, these efforts have not seen a sign - a sign of progress and development, which means, it is necessary to increase output menajamen improvement.The method used was a demonstration and practice. Demonstrations conducted at the stage of the introduction of tools to etalworkers, while the practice is performed immediately after the target is considered to use a tool that is prepared to increase production.Activity Results: Effectiveness and efficiency of technology tools / lathe versatile mechanical system seen from the large expenses associated with the manufacture of the benefits calculated by financially. (1) Changes in the behavior of workers before and after using the technology tools / lathe versatile mechanical system. (2) The increase in family income before and after using the technology.